2002
DOI: 10.1002/ajmg.10626
|View full text |Cite
|
Sign up to set email alerts
|

Dysmorphic features and learning disability in an adult male with pure partial trisomy 17q24‐q25 due to a terminal duplication

Abstract: We describe an adult male with severe learning disability, epilepsy, and dysmorphic features. Cytogenetic studies demonstrated a terminal duplication of the long arm of chromosome 17, resulting in partial trisomy 17q24-q25. Our patient shows some of the characteristic features of the distal 17q phenotype, but in addition has more unusual features such as epilepsy, sensorineural hearing loss, and long fingers and overlapping toes. We suggest that these features occur with terminal duplications of 17q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…As in previously described cases (17,18,19,20,21,22), this patient has short stature. Our patient, like previously described patients, has a disproportionate dwarfism because of rhizomelic shortening of the extremities, which usually would not be consistent with a disorder of the GH-IGF1 axis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As in previously described cases (17,18,19,20,21,22), this patient has short stature. Our patient, like previously described patients, has a disproportionate dwarfism because of rhizomelic shortening of the extremities, which usually would not be consistent with a disorder of the GH-IGF1 axis.…”
Section: Discussionsupporting
confidence: 79%
“…Similar de novo distal 17q duplications have been reported in several cases (17,18,19,20,21,22), two of whom were mosaics (17,18,19,20). All these reported patients (except one with a relatively small duplication (21)) were short.…”
Section: Introductionsupporting
confidence: 77%
“…6 Mental and growth retardation, microcephaly, high forehead, frontal bossing, temporal retraction, short and broad nose, broad and flat nasal bridge, large mouth with down-turned corners, thin upper lip, cleft palate, low-set and malformed ears, short and webbed neck, limb shortness and skeletal anomalies, abnormalities of genital, brain, heart and kidney were reported in partial trisomy17q patients. 6,7 Cordier et al first reported a combination of partial trisomy 17q and monosomy 5p in fetus. 8 In this case, nearly every phenotypic sign observed prenatally on the ultrasound scan.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, 32 cases of partial trisomy for the distal region of 17q were reported either inherited or de novo. [2][3][4][5][6][7][8] A derivative chromosome 4 due to partial trisomy of chromosome 17q has never been described, to our knowledge. We demonstrated that the fetus was a carrier of a de novo derivative chromosome 4 arising from partial trisomy 17q.…”
mentioning
confidence: 99%
“…Manifestations of this anomaly include psychomotor/mental retardation, growth retardation, and dysmorphic features such as facial asymmetry with hypertelorism, frontal bossing and temporal narrowness, a broad nasal bridge, epicanthal folds, wide mouth with a thin upper lip, micrognathia, webbed neck, low-set posteriorly angulated ears, and an abnormal hairline. Moreover partial trisomy 17q is associated with polydactyly, long fingers, abnormal positioned feet, cerebellar hypoplasia, multiple cardiac anomalies, limb shortness, hyperlaxity, genital abnormalities, and accessory spleen [6,7].…”
mentioning
confidence: 99%